7: STATUS OF WILD TURKEYS IN MICHIGAN - F. J. Ignatoski (Wildlife Society Bulletin)
ABSTRACT In the fall of 1969, Michigan had an estimated turkey population of 4,000, descendants of more than 800 game‐farm turkeys stocked between 1954 and 1958. Successful annual hunting seasons had been held each year since 1965; by the close of the spring 1970 season, 701 turkeys had been taken, Mortality due to weather and disease was minimal. Turkeys were most abundant in the oak‐forest habitat.